Systematic scheme for performance measurement in display–camera-based sensing networks. (October 2017) - Chen, Changsheng; Mow, Wai Ho
Camera-based wireless video sensor networks present opportunities to use large numbers of low-cost, low-resolution wireless camera sensors for various applications such as outdoor remote surveillance and ubiquitous data transmission in line-of-sight systems. Owing to the continuously increasing popularity of displays and cameras, communication in sensor networks with display–camera pairs has become a promising area in both computer vision and wireless communication communities. However, measurement/sampling procedures for sensing data in wireless video sensor networks have not been established well yet. Consistency in channel measurements is an open issue, as precise calibration of the experimental settings has not been fully studied in the literature. This article focuses on establishing a scheme for the precise calibration of the display–camera channel performance. To guarantee high consistency in the experiment, we propose an accurate measurement scheme for the geometric parameters and identify some unstable channel factors such as the Moire effect, rolling-shutter effect, blocking artifact, inconsistencies in autofocus, trembling, and vibrations. In the experiment, we first define the consistency criteria based on the error-prone regions in the bit error rate plots of the channel measurements. It is demonstrated that the consistency of the experimental results can be improved by the proposed precise calibration scheme.